Top Challenges from the first Practical Online Controlled Experiments Summit - Fabijan, Aleksander (SIGKDD Explorations June 2019: Volume 21, Issue 1, 2019)
Online controlled experiments (OCEs), also known as A/B tests, have become ubiquitous in evaluating the impact of changes made to software products and services. While the concept of online controlled experiments is simple, there are many practical challenges in running OCEs at scale and encourage further academic and industrial exploration. To understand the top practical challenges in running OCEs at scale, representatives with experience in large-scale experimentation from thirteen different organizations (Airbnb, Amazon, Booking.com, Facebook, Google, LinkedIn, Lyft, Microsoft, Netflix, Twitter, Uber, Yandex, and Stanford University) were invited to the first Practical Online Controlled Experiments Summit. All thirteen organizations sent representatives. Together these organizations tested more than one hundred thousand experiment treatments last year. Thirty-four experts from these organizations participated in the summit in Sunnyvale, CA, USA on December 13-14, 2018. While there are papers from individual organizations on some of the challenges and pitfalls in running OCEs at scale, this is the first paper to provide the top challenges faced across the industry for running OCEs at scale and some common solutions.